Implementation of Ethnomathematics in Banten Mukarnas Batik Motifs in Improving Students' Mathematical Creative Thinking Skills at MTs Al-Khairiyah Rancaranji Padarincang - Kusuma, Jaka Wijaya; Caesarani, Sarah; Wulandari, Resi (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to explore the implementation of Ethnomathematics of Banten Mukarnas batik motifs in improving students' mathematical reasoning and creative thinking skills. Ethnomathematics was chosen to connect mathematical concepts with local culture so that students can see the relevance of mathematics in everyday life. The method used in this study is a quasy experiment with a Pretest-Postest Control Group Design. The sample was selected using random sampling technique. The data collection technique was carried out by providing test questions for students' mathematical creative thinking ability. The analysis was carried out quantitatively on the learning process and measuring students' creative thinking skills before and after the application of Ethnomathematics. From the results of the posttest data analysis of the experimental and control classes, the sig. (2-tailed) of 0.001 < 0.05 and an average of 89.42 in the experimental class, while in the control class, the average was 76.61. So, it can be concluded that there is a difference in the ability of students to think creatively and mathematically using the ethnomathematics-based learning model assisted by the Banten Mukarnas batik motif compared to students who obtain the conventional learning model